Virulência de Nomuraea rileyi (Farlow) Samson e sua relação com a estrutura e composição cuticular de lavar de lepidópteros-praga - Fronza, Edegar (My University, 2014)
Nomuraea rileyi is an entomofungus that mainly infects lepidopteran representatives of the Noctuoidea superfamily, which includes key-pests of various crops of large economic importance. Nevertheless, the susceptibility of species in relation to this agent is variable, even among representatives of the same family or genus. One of the factors responsible for this differentiated susceptibility might be the lipid composition of the larval cuticle. The aim of this study was to assess the cuticular structure and composition of lepidopteran larvae and their relationship with the susceptibility to N. rileyi fungi. The species Anticarsia gemmatalis, Mythimna sequax, Rachiplusia nu and Spodoptera cosmioides and two strains of the fungus (CH87551 and UB93150) were used. Second instar larvae were obtained from the mass creation of the Pest Control Laboratory at the University of Caxias do Sul and subjected to suspensions of 107, 108 and 109 conidia/mL for 24 hours and subsequently transferred to 200mL containers containing specific artificial diets. The bioassays were maintained in controlled conditions and assessed daily for 14 days. In order to perform an analysis of the cuticular lipid composition, exuviae derived from the larval-pupal metamorphosis were subjected to extraction with hexane and with dichloromethane-methanol afterwards. For obtaining the M. sequax exuviae, the larvae were fed with Lolium multiflorum. The obtained extracts were analyzed by means of slender layer chromatography and their components were separated using open column chromatography components, whose resulting fractions were analyzed through gas chromatography attached to mass detector (GCMS). Images of scanning electron microscopy (SEM) were obtained from second instar larvae of each species, subjected to a suspension of 108 conidia/mL and analyzed 24, 48 and 72 hours after exposure to the pathogen. The results showed that the assessed species were differently affected by N. rileyi fungi or even by different assessed strains. The LC50 (log dose) obtained with the CH and UB strains was 6,73 and 7,97 for A. gemmatalis and 8,26 and 9,16 for R. nu respectively. S. cosmioides was susceptible only to the UB strain, but the mortality was limited to 11.5% in the highest concentration and M. sequax was not susceptible to any of the assessed strains. The cuticular lipid composition showed qualitative and quantitative differences between the larvae. The main components identified in A. gemmatalis, M. sequax and R. nu were hydrocarbons, accounting for 72,3, 74,5 and 83,6% respectively, with lower diversity of compounds for M. sequax. Linear and branched fatty acids (C14 to C20) have been identified, with different compositions in each one of the species. It was found an aldehyde and a fatty alcohol in A. gemmatalis and other fatty aldehyde in R. nu. In S. cosmioides, the major identified component was vitamin E, with more than 70%. In the SEM images, it was possible to observe conidia of N. rileyi attached to the cuticular surface of the four assessed species, especially in the abdominal region and in pseudopods, even after 48 hours of contact, mainly in S. cosmioides and M. sequax, species in which many observed conidia showed germ tube growing in tandem with the surface. The species that were more likely in these bioassays were the ones that presented, in addition to large amounts of alkanes, the greatest diversities of these compounds. The less susceptible species showed little quantity and/or variety of alkanes or even some antioxidant compound, as in the case of the vitamin E. The obtained results suggest that, besides differences in the lipid composition and cuticular structure of the larvae, the variability of N. rileyi might be related to the differentiated susceptibility observed in species, however, the potential usage of this agent as a tool for holding an integrated pest management is sizeable and needs to be better understood and explored.
Nomuraea rileyi é um entomofungo que infecta principalmente lepidópteros representantes da superfamília Noctuoidea, que inclui pragas-chave de diversas culturas de grande importância econômica. No entanto, a susceptibilidade das espécies a este agente é variável, mesmo entre representantes da mesma família e até de mesmo gênero. Um dos fatores responsáveis por esta susceptibilidade diferenciada pode ser a composição lipídica da cutícula larval. O objetivo deste estudo foi avaliar a estrutura e composição cuticular de larvas de lepidópteros e sua relação com a susceptibilidade a N. rileyi. Foram utilizadas as espécies Anticarsia gemmatalis, Mythimna sequax, Rachiplusia nu e Spodoptera cosmioides e duas linhagens do fungo (CH87551 e UB93150). Larvas de segundo instar foram obtidas a partir da criação massal no Laboratório de Controle de Pragas da Universidade de Caxias do Sul e submetidas a suspensões de 107, 108 e 109 conídios/mL por 24 horas e após, transferidas para recipientes de 200mL contendo dietas artificiais específicas. Os bioensaios foram mantidos em condições controladas e avaliados diariamente por 14 dias. Para análise da composição lipídica cuticular, exúvias oriundas da metamorfose larval-pupal foram submetidas à extração com hexano e posteriormente à diclorometano-metanol. Para obtenção das exúvias de M. sequax, as larvas foram alimentadas com Lolium multiflorum. Os extratos obtidos foram analisados por cromatografia de camada delgada e seus componentes separados por cromatografia em coluna aberta, cujas frações resultantes foram analisadas por cromatografia gasosa acoplada a detector de massas (GCMS). Imagens de microscopia eletrônica de varredura (MEV) foram obtidas de larvas de segundo ínstar de cada espécie, submetidas uma suspensão de 108 conídios/mL e analisadas 24, 48 e 72 horas após a exposição ao patógeno. Os resultados demonstraram que as espécies avaliadas foram diferentemente afetadas por N. rileyi e, mesmo pelas diferentes linhagens avaliadas. A CL50 (log dose) obtida com as linhagens CH e UB foi de 6,73 e 7,97 para A. gemmatalis e 8,26 e 9,16 para R. nu respectivamente. S. cosmioides foi susceptível apenas à linhagem UB, porém a taxa de mortalidade foi de apenas 11,5% na maior concentração e M. sequax não foi susceptível a nenhuma das linhagens avaliadas. A composição lipídica cuticular apresentou diferenças quali-quantitativas entre as larvas. Os principais componentes identificados em A gemmatalis, M. sequax e R nu foram hidrocarbonetos, respondendo por 72,3, 74,5 e 83,6% respectivamente, com menor diversidade de compostos para M. sequax. Ácidos graxos lineares e ramificados (C14 a C20) foram identificados, com diferentes composições em cada uma das espécies. Identificou-se um aldeído e um álcool graxo em A. gemmatalis e outro aldeído graxo em R. nu. Em S. cosmioides, o componente majoritário identificado foi vitamina E, com mais de 70%. Nas imagens de MEV foi possível observar conídios de N. rileyi aderidos à superfície cuticular das quatro espécies avaliadas, especialmente na região abdominal e nos pseudopodes, mesmo depois de 48 horas após contato, sobretudo em S. cosmioides e M. sequax, espécies nas quais muitos dos conídios visualizados apresentaram tubo germinativo crescendo paralelamente à superfície. As espécies que se mostraram mais susceptíveis nestes bioensaios foram as que apresentaram, além de grandes quantidades de alcanos, as maiores diversidades destes compostos. As espécies menos susceptíveis apresentaram pouca quantidade e/ou variedade de alcanos ou ainda algum composto antioxidante, como no caso da vitamina E. Os resultados obtidos sugerem que, além das diferenças na composição lipídica e na estrutura cuticular das larvas, a variabilidade de N. rileyi pode estar relacionada à susceptibilidade diferenciada observada nas espécies, no entanto o potencial de uso deste agente como ferramenta no manejo integrado de pragas é considerável e precisa ser mais bem compreendido e explorado.
Keywords: Fungos entomopatogênicos; Fungos como agentes no controle biológico de pragas; Virulência (Microbiologia); Biotecnologia